Structural-visual functional relationships detected by optical coherence tomography in varying age-cohorts’ patients with optic neuritis - Shi, Wei; Zuo, Hua-Xin; Li, Si-Yuan; Zheng, Pan-Pan; Xu, Quan-Gang; Cai, Si-Yu; Wei, Shi-Hui; Li, Li; Peng, Chun-Xia (International journal of ophthalmology, 2022)
AIM: To assess the relationships of final best-corrected visual acuity (BCVA) and the optic nerve structural loss in varying age-cohorts of optic neuritis (ON) patients. METHODS: This is a retrospective, cross-sectional study. Totally 130 ON subjects (200 eyes) without ON onset within 6mo were included, who underwent BCVA assessment, peripapillary retinal nerve fibre layer (pRNFL) and macular segmented layers evaluation by optical coherence tomography (OCT). RESULTS: For the 0-18y cohort, the final BCVA (logMAR) was significantly better and less frequent recurrences than adult cohorts (P=0.000). The final BCVA (logMAR) in all age-cohorts of the ON patients had negative and linear correlations to the pRNFL thicknesses and macular retinal ganglion cell layer (mRGCL) volumes, when the pRNFL thicknesses were reduced to the thresholds of 57.2-67.5 µm or 0.691-0.737 mm3 in mRGCL volumes, respectively, with the strongest interdependence in the 19-40y cohort. The ON patients from varying age cohorts would be threatened by blindness when their pRNFL thicknesses dropped 36.7-48.3 µm or the mRGCL volumes dropped to 0.495-0.613 mm3. CONCLUSION: The paediatric ON has best prognosis and young adult ON exhibits perfectly linear correlations of final vision and structural loss. The pRNFL and the mRGCL could be potential structural markers to predict the vision prognosis for varying-age ON patients.